Enhanced laser absorption from radiation pressure in intense laser plasma interactions. (6th June 2017) - Dollar, F; Zulick, C; Raymond, A; Chvykov, V; Willingale, L; Yanovsky, V; Maksimchuk, A; Thomas, A G R; Krushelnick, K
Abstract: The reflectivity of a short-pulse laser at intensities of 2 × 10 21 Wcm − 2 with ultra-high contrast ( 10 − 15 ) on sub-micrometer silicon nitride foils was studied experimentally using varying polarizations and target thicknesses. The reflected intensity and beam quality were found to be relatively constant with respect to intensity for bulk targets. For submicron targets, the measured reflectivity drops substantially without a corresponding increase in transmission, indicating increased conversion of fundamental to other wavelengths and particle heating. Experimental results and trends observed in 3D particle-in-cell simulations emphasize the critical role of ion motion due to radiation pressure on the absorption process. Ion motion during ultra-short pulses enhances the electron heating, which subsequently transfers more energy to the ions.